Effect of electroacupuncture on vascular remodeling in rats with cerebral ischemia by regulating irisin based on VEGF/Akt/eNOS signaling pathway - Lu Cao; Wenchao Ding; Yashuo Feng; Chong Guan; Li Liu; Hongyu Xie; Kewei Yu; Dongyan Xu; Lijuan Zhao; Xuan Sha; Xiaoman Deng; Santian Wu; et al. (Brain Research Bulletin)
Objective: This study aimed to explore the cumulative effects and expression patterns of electroacupuncture (EA) on irisin secretion, observe the effects of EA on the recovery of neurobehavioral function and vascular remodeling after cerebral ischemia, and elucidate the mechanism by which EA promotes vascular remodeling by regulating irisin expression. Methods: A rat model of left middle cerebral artery occlusion (MCAO) was prepared, and EA was performed. Tissue distribution and expression of irisin were determined by immunofluorescence, enzyme-linked immunosorbent assay (ELISA), and Western blotting. Type III fibronectin domain protein 5-silenced adeno-associated virus (rAAV-shFNDC5) was injected into the lateral ventricle as a control. Neurobehavioral function was evaluated using 2,3,5-triphenyltetrazolium chloride (TTC) staining and behavioral experiments, while vascular remodeling was evaluated using laser speckle blood flow imaging, and the expressions of irisin and vascular remodeling-related factors were measured by ELISA and Western blotting. Results: The number of FNDC5-positive neurons, fluorescence intensity, and irisin expression reached their maximum increase after 7 days of EA treatment. In addition, the EA group exhibited a significant reduction in cerebral infarct volume and impairment of neurobehavioral function, an increase in cerebral blood flow and microvascular diameter on the ischemic side, and significantly higher expression levels of FNDC5, brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF), protein kinase B (Akt), and endothelial nitric oxide synthase (eNOS). However, rAAV-shFNDC5 significantly weakened the therapeutic effects of EA. Conclusions: EA upregulated irisin expression, reaching a peak after 7 days of EA and then stabilizing. EA facilitated vascular remodeling after cerebral ischemia, and this might be associated with the activation of the irisin-mediated VEGF/Akt/eNOS signaling pathway.